RETRACTED: ZFP36 Binds With PRC1 to Inhibit Tumor Growth and Increase 5-Fu Chemosensitivity of Hepatocellular Carcinoma - Chen, Weiqian; Chen, Minjiang; Zhao, Zhongwei; Weng, Qiaoyou; Song, Jingjing; Fang, Shiji; Wu, Xulu; Wang, Hailin; Zhang, Dengke; Yang, Weibin; Wang, Zufei; Xu, Min; et al. (Frontiers in Molecular Biosciences, 2020)
Hepatocellular carcinoma (HCC) is the fifth common cause of tumor-related death worldwide. ZFP36, a RNA-binding protein, decreases in many cancers and its role in HCC remains unclear. This study aimed to investigate the underlying mechanisms by which ZFP36 inhibited HCC progression and increased fluorouracil (5-Fu) sensitivity. We found that ZFP36 was downregulated and PRC1 was upregulated in HCC tissues compared with adjacent non-tumor tissues. In vitro investigation presented that ZFP36 acted as a tumor suppressor, while overexpression of PRC1 increased cell proliferation, colony formation and invasion. Further investigations demonstrated that overexpression of ZFP36 inhibited tumor growth and promoted 5-Fu sensitivity in xenograft tumor mice model, which could be reversed when PRC1 overexpressed simultaneously. Luciferase reporter assays and Ribonucleoprotein immunoprecipitation analysis indicated that ZFP36 could bind to adenylate uridylate-rich elements located in PRC1 mRNA 3′UTR to downregulate PRC1 expression. Taken together, our findings identified that ZFP36 regulated PRC1 to exert anti-tumor effect, which suggested a potential therapeutic strategy for treating HCC by exploiting ZFP36/PRC1 axis.